Innovation Conundrum in Antimicrobial Sector: A Curious Case for Intellectual Property Rights (Journal of Intellectual Property Rights (JIPR), 2024)
Innovation in the antimicrobial sector has become challenging as the conventional incentive models, including intellectual property rights (IPR), fail to produce expected outcomes. Due to growing antimicrobial resistance, a persistent demand for new antimicrobials exists. However, relatively high risk and low return from the investment in antimicrobial drug development and the shorter period of use of antimicrobial drugs (as the drug of last resort) make the antimicrobial sector less attractive for investors. Moreover, antimicrobial resistance stewardship plans discourage the excessive use of antibiotics, impacting sales volumes. As a result, the limited-term monopoly of patents does not provide adequate protection for investors to recoup their investments. The R&D pipelines for antimicrobial drugs have dried up because of the reluctance among the investors and the absence of Big Pharma, and the new incentive models with a pull-and-push approach are gaining momentum. The policy interventions for antimicrobial drug development entrench between two continuums: innovation and access. The innovation structure demands novel approaches based on new/alternative incentive models at the pre-clinical and clinical stages. Patent licensing strategies could facilitate innovation and access to antimicrobial drugs, such as open and non-exclusive patent licensing and patent pooling. Given the disparities among the nations in their approach to antimicrobial resistance and antimicrobial drug development, a global health and innovation initiative with a cross-sectional and coordinated approach is pertinent. The policy interventions for antimicrobial innovation need a long-term crosssectionaland mission-oriented approach.